Engineering Nitrogen Fixation Activity in an Oxygenic Phototroph - Deng Liu (American Society for Microbiology, 2018)
ABSTRACT Biological nitrogen fixation is catalyzed by nitrogenase, a complex metalloenzyme found only in prokaryotes. N2 fixation is energetically highly expensive, and an energy-generating process such as photosynthesis can meet the energy demand of N2 fixation. However, synthesis and expression of nitrogenase are exquisitely sensitive to the presence of oxygen. Thus, engineering nitrogen fixation activity in photosynthetic organisms that produce oxygen is challenging. Cyanobacteria are oxygenic photosynthetic prokaryotes, and some of them also fix N2. Here, we demonstrate a feasible way to engineer nitrogenase activity in the nondiazotrophic cyanobacterium Synechocystis sp. PCC 6803 through the transfer of 35 nitrogen fixation (nif) genes from the diazotrophic cyanobacterium Cyanothece sp. ATCC 51142. In addition, we have identified the minimal nif cluster required for such activity in Synechocystis 6803. Moreover, nitrogenase activity was significantly improved by increasing the expression levels of nif genes. Importantly, the O2 tolerance of nitrogenase was enhanced by introduction of uptake hydrogenase genes, showing this to be a functional way to improve nitrogenase enzyme activity under micro-oxic conditions. To date, our efforts have resulted in engineered Synechocystis 6803 strains that, remarkably, have more than 30% of the N2 fixation activity of Cyanothece 51142, the highest such activity established in any nondiazotrophic oxygenic photosynthetic organism. This report establishes a baseline for the ultimate goal of engineering nitrogen fixation ability in crop plants. IMPORTANCE Application of chemically synthesized nitrogen fertilizers has revolutionized agriculture. However, the energetic costs of such production processes and the widespread application of fertilizers have raised serious environmental issues. A sustainable alternative is to endow to crop plants the ability to fix atmospheric N2 in situ. One long-term approach is to transfer all nif genes from a prokaryote to plant cells and to express nitrogenase in an energy-producing organelle, chloroplast, or mitochondrion. In this context, Synechocystis 6803, the nondiazotrophic cyanobacterium utilized in this study, provides a model chassis for rapid investigation of the necessary requirements to establish diazotrophy in an oxygenic phototroph.